Practical nurses’ experiences of client and patient information systems support for performance - cross-sectional study - Saranto, Kaija; Ikonen, Johanna; Koponen, Samuli; Kyytsönen, Maiju; Kinnunen, Ulla-Mari; Vehko, Tuulikki (Finnish Journal of eHealth and eWelfare, 2023)
The support provided by client and patient information systems for the performance of social and health care work tasks has previously been studied among doctors, nurses, and highly qualified social professionals. The research targeted at practical nurses is a continuation of these studies. The research focused on how client and patient information systems support the work, cooperation and flow of information of practical nurses and how useful they assess these information systems in their work.The online survey was forwarded to practical nurses of working age in the register of members of the Finnish Federation of Local and Basic Caregivers (SuPer ry) and the Union of Public and Welfare Sectors (JHL) in spring 2022. Averages and percentages of the material were calculated. The amount of 3866 practical nurses responded to the electronic survey from all wellbeing services counties and Åland. The average age of respondents was 49 years and the majority of respondents spoke Finnish as their mother tongue (92.9%). Most of the practical nurses worked in social welfare. About one third (27.9%) had more than 20 years of work experience. Practical nurses estimated themselves to be an experienced user of information systems. Half (50-64 %) of practical nurses in different settings reported that information systems help to ensure continuity of care when it comes to identifying the benefits associated with information systems. A key problem was that the use of IT systems takes too much working time from clients. Practical nurses felt that the information systems mainly supported their work. However, they reported deficiencies in the ability of the information system to produce a summary of the patients’ health status. While information systems supported the exchange of information within their own organisation, there were challenges in the exchange of information between social and healthcare organisations. The support of information systems for the exchange of information between clients or their relatives was poor. In addition to information systems, telephone and papers were used on a weekly basis. Neither the regional information systems nor Kanta services were the usual means of exchanging information in the work of practical nurses. The assessments of the information systems by practical nurses were rather positive. Support for information-search in the exchange of information between organisations and experience that summaries should be more supportive for work confirmed earlier results from surveys. Information systems’ support for the work is highlighted in the current context were staff shortages and growing service needs pose challenges to new welfare areas.